Carotid Intima-Media Thickness (cIMT) and Cognitive Performance: A Population-Based Cross-Sectional Study From North India. (23rd January 2023) - Vibha, Deepti; Prasad, Kameshwar; Dwivedi, Sada Nand; Kant, Shashi; Pandit, Awadh Kishor; Tiemeier, Henning; Srivastava, Achal Kumar; Karthikeyan, Ganesan; Garg, Ajay; Verma, Vivek; Kumar, Amit; Nehra, Ashima; et al.
Abstract : Introduction: Atherosclerosis has been shown to impact cognitive impairment, with most of the evidence originating from European, African, or East Asian populations that have employed carotid intima-media thickness (cIMT) as a biomarker for atherosclerosis. Vascular disease is related to dementia/cognitive decline. There is no community-based study from India that has looked at the association of cIMT with cognitive performance. Methods: In this cross-sectional study between December 2014 and 2019, we recruited 7505 persons [(mean age 64.6 (9.2) y) and 50.9% women] from a community-dwelling population in New Delhi. These persons underwent carotid ultrasound to quantify cIMT and a cognitive test battery that tapped into memory, processing speed, and executive function. We also computed the general cognitive factor (g-factor), which was identified as the first unrotated component of the principal component analysis and explained 37.4% of all variances in the cognitive tests. We constructed multivariate linear regression models adjusted for age, sex, education, and cardiovascular risk factors. Additional adjustment was made for depression, anxiety, and psychosocial support in the final model. Results: We found a significant association of higher cIMT with worse performance in general cognition (β=−0. 01(95% CI: −0.01; −0.01); P <0.001), processing speed (β=−0.20; 95% CI: −0.34; −0.07); P =0.003), memory (β=−0.29; 95% CI: −0.53; −0.05); P =0.016), and executive function (β=−0.54; 95% CI: −0.75; −0.33); P =<0.001). There was no statistically significant association of cIMT with Mini-Mental Status Examination score (β=0.02; 95% CI: −0.34; 0.40; 0.89). Conclusion: The cross-sectional study found significant associations of increased cIMT with worse performance in global cognition, information processing, memory, and executive function.